Perbandingan Quantity Take Off (QTO) Material Berbasis Building Information Modeling (BIM) Terhadap Metode Konvensional pada Struktur Pelat - Asih, Windi Retno; Bayzoni, Bayzoni; Husni, Hasti Riakara; Niken, Chatarina (Universitas Lampung, 2022)
This study aims to determine the results of the Quantity Take Off (QTO) based on Building Information Modeling (BIM) and compare them with conventional calculations on slab structures. With a case study of the Integrated Surgical Care Building at RSUD Dr. H. Abdul Moeloek (Zone A). Building modeling is done using Autodesk Revit software. Based on the modeling results, the concrete volume for the slab structure is 888.99 m3 , which is 1.67% more effective than the conventional method. The value of slab structure reinforcement material is 119,762.03 kg, with a result of 3.32% more effective than conventional methods. BIM-based quantity take off able to estimate material in detail up to the calculation of waste material. The results of the calculation of the Waste Material Ratio (WMR) for the slab structure reinforcement is 2.48% from the total procurement of 122,814.28 kg, with an estimated waste material of 3,049.23 kg. Based on this research, it can be concluded that the BIM-based quantity take-off is able to calculate material volume in detail, and supports the calculation of estimated waste material.